RESCISSION OF DIVIDENDS. - Briggs, L. L. (The Accounting Review, 1932)
When the board of directors of a corporation declares dividends it generally makes them payable at a future date and when that date arrives the distribution to the stockholders usually is made according to the terms of the resolution. However, between the date of declaration and the time set for payment, the corporation may have reverses which leave it in such condition that conservative financial policy would decree that nothing be paid to the shareholders. It has been held that the declaration of cash dividend severs the amount from corporate funds and creates a debt on the part of the corporation in favor of its stockholders and this debt cannot be rescinded against the will of any stockholder so far as he is concerned. But if a board of directors should declare a cash dividend and make a public announcement of the fact, the courts have held that thereafter the board has no right to reconsider and rescind its action. Insolvency of the corporation occurring before payment made no difference in the obligation of the company to carry out its dividend declaration and gave the concern no right to rescind the unpaid dividend debt.